Consortia to Promote Access to Medical Information: Some Experiences of the Indian Council of Medical Research - Ratnakar, K.V.; Satyanarya, K; Prema, Prema (DESIDOC Journal of Library & Information Technology, 2010)
Financial crunch and ever rising cost of journals have constrained many scientific/research libraries, especially the medical libraries, to satiate the demands of the users forcing them adopt to new technologies to overcome the challenge of ever rising information demands of the users. In the recent years, library consortium has emerged as a viable solution for resource sharing among libraries. This paper is an overview of the consortia initiated by the Indian Council of Medical Research to share the resources of its medical libraries among its 25 institutes. http://dx.doi.org/10.14429/djlit.29.263